An analysis of heavy rainfall events over the Limpopo River Basin in southern Africa, their moisture sources and pathways - Rapolaki, Ramontsheng Sakia (Department of Oceanography, 2020)
Severe flooding events in subtropical southern Africa are not uncommon and can cause damage to infrastructure, lead to huge economic losses, and fatalities. Although extreme rainfall events can have far-reaching negative consequences, they can also provide large amounts of freshwater within a short time span, which supports the rain-fed farming upon which much of the population depends. However, the mechanisms through which extreme rainfall is produced in southern Africa are still not well understood. In particular, relatively little is known about where the moisture, a key ingredient in the rainfall, is sourced and how it is transported into the region. This thesis aims to address some of the gaps in this understanding by examining the moisture sources and subsequent moisture transport moisture into one of the key river basins in southern Africa, the Limpopo River Basin (LRB). The LRB, located in eastern southern Africa and spanning four countries, has experienced a number of extreme flooding events over the last three decades. Using CHIRPS satellite merged rainfall data for 1981-2016, the thesis identified the top 200 heavy extreme rainfall events in the LRB and the associated weather systems. It was found that tropicalextratropical cloud bands account for almost half of the events and tropical lows are responsible for just over a quarter. The remaining quarter of the events are associated with mesoscale convective systems and cut-off lows, the latter more important during transition seasons. Most of the events occur in the late summer when tropical lows and cloud bands are more common. Some relationships between the frequency of heavy rainfall events over the LRB and interannual climate modes of variability such as ENSO, SIOD, and SAM were found. Having examined the annual cycle of the top 200 heavy rainfall events, the analysis then applied the Lagrangian trajectory model HYSPLIT, with NCEP II reanalysis data as input, to backtrack air parcels from the LRB to their moisture source on seasonal scales and in terms of the types of weather systems involved. The resulting trajectories show that the seasonal transport of moisture over the LRB originates from seven moisture source regions; namely, local continental, tropical southeast Atlantic Ocean, midlatitude South Atlantic Ocean, tropical Northwest Indian Ocean, tropical southwest Indian Ocean, subtropical southwest Indian Ocean, and the Agulhas Current. Important differences in moisture source regions and pathways exist between early (OctoberDecember) and late (January-April) summers, with the tropical northwestern Indian Ocean and the northern Agulhas Current sources more prominent during JFMA than OND. Generally, moisture v source regions and transport pathways for LRB tend to be influenced by both the regional summer season circulation and the synoptic systems involved. Thus, it was found that cloud band and tropical low events within the top 200 tend to have the Congo Basin as an important moisture source whereas this source is less evident for cut-off low events. To help assess the robustness of the composite synoptic approach, the final part of the thesis applied the Lagrangian analysis to the most severe case in the top 200 events over the LRB (11- 21 January 2013). It was found that this case was largely linked to three main moisture sources: (1) tropical northwest Indian Ocean, (2) the Agulhas Current / Mozambique Channel, subtropical Southwest Indian Ocean, and (3) continental sources over the Congo Basin and northern Tanzania. Generally, the moisture source regions and pathways for the January 2013 event agreed with the climatological moisture source regions over the LRB, apart from the obvious absence of the tropical southeast Atlantic source in this case. In general, the thesis has provided a better understanding of the characteristics of heavy rainfall events over the LRB in terms of their associated weather systems, seasonality, interannual variability, and moisture source regions and trajectories.